The Development of Animation Videos Based Flipped Classroom Learning on Heat and Temperature Topics - Sumarni, Ria Asep; Bhakti, Yoga Budi; Astuti, Irnin Agustina Dwi; Sulisworo, Dwi; Toifur, M (Universitas Islam Negeri Raden Intan Lampung, 2020)
The ability to solve physics problems is still relatively low. Students more often directly use mathematical equations without performing concept understanding analysis. Therefore, learning strategies and media are suitable for physics learning. The purpose of this research is to develop interactive animated videos combined with flipped classroom learning models. This research uses Research and Development (R and D) methods, with 4D development models. The average validation test results are 90,91%, with a good category. So, the animation physics video can use in a flipped classroom. This physics animation video makes it easier for students to learn temperature materials and their changes without being limited by space and time. These physics learning animation videos are highly interactive and can explain abstract physics concepts and integrate with flipped classrooms.